2012
DOI: 10.3727/096368911x576018
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Gel Improves the Survival of Transplanted Myoblasts

Abstract: Duchenne muscular dystrophy (DMD) is the most frequent muscular dystrophy in children and young adults. Currently, there is no cure for the disease. The transplantation of healthy myoblasts is an experimental therapeutic strategy, since it could restore the expression of dystrophin in DMD muscles. Nevertheless, this cellular therapy is limited by immune reaction, low migration of the implanted cells, and high early cell death that could be at least partially due to anoikis. To avoid the lack of attachment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Many approaches have been investigated to enhance myoblast survival upon transplantation, including hypoxia preconditioning; heat shock; and coinjection with small molecules (dextran sulfate), biomaterials (fibrin gel), or macrophages [46][47][48][49][50]. Interestingly, C/EBPb is a potent prosurvival factor [37,38] and is upregulated in several tumors, demonstrating its role as an important mediator of cell survival during tumorigenesis [30,38].…”
Section: Discussionmentioning
confidence: 99%
“…Many approaches have been investigated to enhance myoblast survival upon transplantation, including hypoxia preconditioning; heat shock; and coinjection with small molecules (dextran sulfate), biomaterials (fibrin gel), or macrophages [46][47][48][49][50]. Interestingly, C/EBPb is a potent prosurvival factor [37,38] and is upregulated in several tumors, demonstrating its role as an important mediator of cell survival during tumorigenesis [30,38].…”
Section: Discussionmentioning
confidence: 99%
“…The functions of collagen VI pertaining to various cell types also include the promotion of adhesion,1 2 proliferation,3 migration4 and survival 5 44 45. Attachment of cells to the ECM is important for preventing apoptosis,46 which could be particularly relevant for muscle disorders that directly involve interactions between matrix and muscle, as is the case for high early implanted cell death, partially due to ‘anoikis’, in cell transplantation treatment of DMD 47. Studies with cultured fibroblasts from patients with UCMD have shown that mutant cells or mutated collagen VI exhibit decreased adherence to their surroundings, emphasising that loss of cell ECM interactions is the key mechanism of collagen VI-related myopathies 2 48.…”
Section: Molecular Diagnosis Pathogenesis and Therapeutic Avenuesmentioning
confidence: 99%
“…Other causes suggested to induce apoptosis of the grafted myoblasts were hypoxia [141] and anoikis [160]. However, experiments trying to control each of the previous factors in mice never prevented the whole cell death, and only minimal enhancements of survival were reported [152,[161][162][163][164]. An exception was the administration of an anti-LFA1 antibody in mice, using transgenic -galactosidase to label the grafted cells [149].…”
Section: The Early Survival Of the Myogenic Cellsmentioning
confidence: 99%